Identification and sequence analysis of cDNA clones expressing proteins for serodiagnosis of strogyloidiasis. - Noordin, Rahmah (Universiti Sains Malaysia, 2013)
Strongyloides stercoralis is a soil-transmitted helminth that can cause long-term infection in humans. Infection by this parasite is becoming increasingly important due to the increase in the number of people who are immunosuppressed either due to various diseases, treatment or organ transplantation. Better diagnostic tests are needed for both acute and chronic strongyloides infection to prevent fatality and mortality due to hyper- or disseminated infections. In this study, a cDNA phage library of Strongyloides stercoralis was immunoscreened to identify clones that were immunoreactive with sera of patients with S.